Severe hypotension during junctional rhythm in a patient with multiple cerebral infarcts. Issue 2 (February 2023) - Misumi, Ikuo; Yamakawa, Makoto; Harada, Masahiro; Sato, Koji; Tabira, Akihisa; Usuku, Hiroki; Tsujita, Kenichi
Abstract: An 82-year-old woman with parkinsonism and Lewy body dementia was re-admitted to our hospital due to convulsions and the recurrence of cerebral infarction. Parasternal transthoracic echocardiography showed normal left ventricular wall thickness and wall motion. To treat marked bradycardia and hypotension, she underwent temporary pacing. However, she lost her consciousness, when her blood pressure could not be measured. Simultaneous electrocardiogram and blood pressure monitoring showed that systolic blood pressure decreased by almost 30 mmHg from sinus rhythm to junctional rhythm. In the present case of acute cerebral infarction, severe hypotension occurred during junctional rhythm possibly contributed by parkinsonism and Lewy body dementia. Learning objective: As patients with junctional rhythm usually have no or mild symptoms, there are no specific guidelines for its evaluation and treatment. However, severe symptoms such as hypotension, cerebral infarction, loss of consciousness, or breathlessness may occur in some cases. Holter electrocardiogram with 24-hour noninvasive blood pressure monitoring may be helpful in such severe cases.